Could a well-designed customs reforms remove the trade-off between revenue collection and trade facilitation? - Gael Raballand; Jean-François Marteau; Edmond Mjekiqi; Thomas Cantens (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper is based on first-hand experience from Customs reforms in Sub Saharan Africa (SSA) and presents unpublished data on the impact of Customs reforms on revenues, trade facilitation, private sector operators and frontline Customs officials' behaviors in Africa. Customs agencies are usually one of the key revenue collection agencies in Africa. Customs officials usually consider trade facilitation measures as a threat for revenue collection and strive to increase control over private sector operators through systematic inspections and checkpoints in order to increase public revenues (in theory). In reality, imports undervaluation remains high as well as smuggling and transit diversion, which result in endemic corruption and increased clearance time and uncertainty. Because many issues lie in the internal weaknesses of Customs agencies, a revised approach to Customs reforms is needed to ensure, first, internal control of the organization and then gradually relax controls on operators and ensure formal trade facilitation. Without internal control and knowledge of the magnitude of the malpractices in most Customs agencies in Africa, private sector differentiation can not happen and therefore formal trade facilitation would remain inexistent, while results in terms of revenue collection will probably be below what can be achieved.
Keywords: F14; H11; H32; 330; Customs; trade facilitation; Nigeria; Cameroon; public sector reform